1999
DOI: 10.4319/lo.1999.44.7.1655
|View full text |Cite
|
Sign up to set email alerts
|

The impact of larval and juvenile fish on zooplankton and algal dynamics

Abstract: The impact of young-of-the-year (YOY) fish predation on zooplankton dynamics and cascading effects down to phytoplankton were studied in lake enclosures using different densities of larval and juvenile European perch (Perca fluviatilis). Two experiments, one in June and one in August, were performed in Lake Dagstorpssjön, a slightly eutrophic lake in Scania, southern Sweden. In our experiments, we found that in August, there was a negative relation between YOY perch density and cladoceran biomass and between Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 36 publications
1
33
2
Order By: Relevance
“…According to many authors, fish have no negative effect on the composition of rotifers (e.g. Akopian et al 1999, Meng & Orsi 1999, Romare et al 1999, Chang et al 2008). Richardson and Bartsch (1997) have also reported that the abundance of K. cochlearis is much reduced in the presence of fish.…”
Section: Discussionmentioning
confidence: 99%
“…According to many authors, fish have no negative effect on the composition of rotifers (e.g. Akopian et al 1999, Meng & Orsi 1999, Romare et al 1999, Chang et al 2008). Richardson and Bartsch (1997) have also reported that the abundance of K. cochlearis is much reduced in the presence of fish.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, fish presence reduced zooplankton biomass and promoted a shift in the zooplankton community composition, especially in high nutrient conditions. We observed a decrease in the abundance of large-bodied zooplankters and an increase in the abundance of small-bodied groups, which are less efficient in controlling phytoplankton biomass (Romare et al 1999, Levine et al 2005, thereby enhancing phytoplanktonic biomass and consequently planktonic net productivity in the Fish+Nut treatment.…”
Section: Discussionmentioning
confidence: 83%
“…Through predation on zooplankton, planktivorous fish may promote increased phytoplankton biomass and reduced water clarity (Scheffer, 1998;. The importance of planktivory in freshwater ecosystems is well illustrated by the structuring role of planktivores in trophic cascading phenomena (e.g., Williams and Moss, 2003;Ta´trai et al, 2003;Blanco et al, 2004), especially young-of-the-year (YOY) fish (Post et al, 1997;Romare et al, 1999;Hansson et al, 2007). This structuring role has been studied in detail in northern temperate lakes (see e.g., Romare et al, 1999;Eklo¨v and VanKooten, 2001;Romare and Hansson, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of planktivory in freshwater ecosystems is well illustrated by the structuring role of planktivores in trophic cascading phenomena (e.g., Williams and Moss, 2003;Ta´trai et al, 2003;Blanco et al, 2004), especially young-of-the-year (YOY) fish (Post et al, 1997;Romare et al, 1999;Hansson et al, 2007). This structuring role has been studied in detail in northern temperate lakes (see e.g., Romare et al, 1999;Eklo¨v and VanKooten, 2001;Romare and Hansson, 2003). However, several authors (e.g., Beklioglu et al, 2007;Teixeira de Mello et al, 2009) argue that the cascading effects of planktivorous fish are much more pronounced in warmer (subtropical and Mediterranean) and shallower lakes (Jeppesen et al, 1997(Jeppesen et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%